VD_FINDINFO Jug / 2015 / 158 vom 20. November 2014 - VD Tribunal cantonal (2014)
PRÉSOMPTION D'INNOCENCE, FIXATION DE LA PEINE, CONCOURS RÉEL, PEINE COMPLÉMENTAIRE | 47 CP, 49 al. 1 CP, 49 al. 2 CP, 10 CPP (CH)